Estudo da oxidação do ácido 2,4-diclorofenaxiacético catalisada por modelos bioinspirados - Silva, Francisco de Assis da (2017)
Inspired by natural catalytic systems, metalloporphyrins and Salen complexes have been used as catalysts for the oxidation of xenobiotics in the presence of several oxygen donors, both in homogeneous and heterogeneous catalysis. These catalysts have been highly efficient and selective in the reactions of different substrates, such as pharmaceuticals and pesticides. In this context, the work developed in this dissertation presents the oxidation studies of 2,4-dichlorophenoxyacetic acid herbicide using ferroporphyrins and Jacobsen catalyst as catalysts of these reactions with several oxygen donors. The results shows that the metalloporphyrin and the complex employed in this study are efficient catalysts for oxidation of 2,4-D in the presence of oxygen donors iodosilbenzene (PhIO), metachloroperbenzoic acid (m-CPBA) and hydrogen peroxide (H2O2) both in homogeneous and heterogeneous. The reactions with the unsupported catalysts achieved higher yields than those obtained with the supported catalysts, which is possibly related to the difficulties of access to the catalytic center imposed by the support. The conversion of 2,4-D reached more than 50% in some systems, and, in general, oxidation reactions with the three oxygen donors were selective promoting the formation of hydroquinone (reactions with PhIO and H2O2) and 3,5- dichlorocatechol (reactions with m-CPBA). One of the products identified in the reactions is a metabolite of 2,4-D produced in vivo systems, indicating that the catalysts used in this study can be considered good models of cytochrome P450 in the oxidation of 2,4-D.